PEMETAAN HUJAN ASAM OLEH KEGIATAN INDUSTRY DI KECAMATAN MEDAN DELI, KOTA MADYA MEDAN, KAWASAN INDUSTRI MEDAN (KIM) - David Leo Tarigan; Rahmawaty Rahmawaty; Yunus Afifuddin (Program studi Kehutanan USU, 2016)
Activities of a factory/industrial pollution may lead around Medan Industrial Area (MIA). Effect of pH changes in industrial activity resulted in rain water in the vicinity of the industries, based on the reason for zoning was made to determine how far the greates impact due to the industrial activity of the pH level of rain fell in the area around Medan Industrial Area (MIA) with the aim to determine the effect of the state of industrial activity in Medan Industrial Estate to the acidity of rain falling in the area around the Medan Industrial Area (MIA). Rainwater harvesting tool mounted in an open area by using graduated observatory type rain. Equipment mounted as high as 120 cm on an open area of land located at the sites. The parameters analyzed were pH, NOX and SOX. Results of observations show that rain water collected in Medan Industrian Estate area tends to be acidic. Keywords: Medan Industrial Area (MIA), acid rain and pH